Citocalasinas produzidas por Xylaria sp., um fungo endofítico de Piper aduncum (piperaceae) - Silva, Geraldo H. [UNESP]; Oliveira, Camila M. de [UNESP]; Teles, Helder L. [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Araújo, Angela Regina [UNESP]; Pfenning, Ludwig H.; Young, Maria Claudia M.; Costa-Neto, Claudio M.; Haddad, Renato; Eberlin, Marcos N. (Sociedade Brasileira de Química, 2010)
A chemical study on the EtOAc extract produced by Xylaria sp., an endophytic fungus from Piper aduncum, resulted in the isolation of a new cytochalasin 1, along with five known 19,20-epoxycytochalasin D (2), C (3), N (4), Q (5), and R (6). The 1-6 were evaluated against the fungi C. cladosporioides and C. sphaerospermum and only 5 showed weak activity. The cytotoxicity in vitro against HeLA and CHO cells lines were investigated and the cytochalasins 2-4, and 6 showed a strong activity against HeLA. The DNAdamaging activity of 1-6 were also investigated against mutant strains of S. cerevisiae.
Cytochalasins produced by Xylaria sp., an endophytic fungus from Piper aduncum
Keywords: Xylaria sp.; Piper aduncum; endophytic fungus